Perception of the creation of an agricultural trader in Mosquera, Colombia - Lechuga Cardozo, Jorge Isaac; Cruz Páez, Fabio Orlando (Cooperativismo & Desarrollo, 2023)
The aim of the research is to appreciate the marketing strategies of small and medium agricultural entrepreneurs in the coverage area of the Center for Agricultural Biotechnology - CB.A. de Mosquera (Cundinamarca) of the National Learning Service-SENA. Thus, the study with a quantitative approach reaches a Cross-Sectional analytical level. As a technique, the survey is used through a questionnaire with items for seven variables: administrator profile, perception of the marketer, marketing strategies and profit management. Once the information has been analyzed, it is found that the managers of agricultural SMEs would like to be an active part of a livestock marketer for the distribution and technology transfer of products with support and association led by the Center for Agricultural Biotechnology. It is concluded that the creation of a livestock trading company with strategic leadership in the commercialization of agricultural products projected to positively impact the quality of life of the communities of the municipality of Mosquera through greater economic, social, and organizational cultural benefits of SMEs in activities such as savings in time and financial resources for marketing, and innovation in the design of its products.